Abacavir use is associated with increased prothrombin conversion - Yan, Qiuting; Huang, Shengshi; van der Heijden, Wouter; Ninivaggi, Marisa; van de Wijer, Lisa; de Laat-Kremers, Romy; Van der Ven, Andre J.; de Laat, Bas; de Mast, Quirijn (Frontiers in Immunology, 2023)
There is ongoing debate as to whether abacavir (ABC) increases the risk for cardiovascular disease(CVD) in people living with HIV (PLHIV) and the mechanisms underlying this possible association. We recently showed that the use of an ABC-containing regimen was independently associated with increased thrombin generation (TG). In the present study, we aim to explore these findings further, by studying the mechanistical processes that underly the global thrombin generation test via thrombin dynamics analysis. Thrombin dynamics analysis can pinpoint the cause of increased thrombin generation associated with ABC-use either to the procoagulant prothrombin conversion pathway or the anticoagulant thrombin inactivation pathway. In this cross-sectional study 208 virally suppressed PLHIV were included, of whom 94 were on a ABC-containing regimen, 92 on a tenofovir disoproxil fumarate (TDF)-containing regimen, and the remainder on other regimens. We used Calibrated Automated Thrombinography to measure thrombin generation and perform thrombin dynamics analysis. The total amount of prothrombin conversion, as well as the maximum rate of prothrombin conversion were significantly increased in PLHIV on an ABC containing regimen compared to other treatment regimens. The levels of pro- and anticoagulant factors were comparable, indicating that the ABC-induced changes affect the kinetics of prothrombin conversion rather than procoagulant factor levels. Moreover, Von Willebrand Factor (VWF), active VWF and VWF pro-peptide levels were significantly higher in PLHIV than controls without HIV. However, they did not differ between ABC and non-ABC treated participants.